PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI MOTIVASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL (Studi pada Aparatur Kelurahan se – Kota Pekalongan) (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study is to reveal the impact of leadership style and working environment on the performance of sub district officials at municipality of Pekalongan, approached the issue by using several variables, i.e motivation, job satisfaction, and organizational commitment . The target population of this study are sub district officials working at Municipality of Pekalongan, consists of 265 people. Purposive sampling used as preferred method and the selected sample consists of 152 people working as sub district officials, all are IVb echelon, were chosen as respondents. Data collection was conducted by using questionnaires which were distributed to 152 respondents. There were 126 questionnaires returned by the participants, 121 of which were in perfect condition to be processed and the rest were broken. The result of this study shows that performance is not directly affected by the leadership style and working environment, but indirectly affected through motivation, job satisfaction, and organizational commitment. Keywords:    Leadership Style, Work Environment, Motivation, Organizational Commitment, Job Satisfaction, Performance.